Optimization method for heat-engine plant thermal on-line process identification and control algorithm based on dual-objective parallel ISLAND-HFC mixed model genetic programming algorithm - MA RUI; PENG GANG; YUAN XIAOLEI; XU XINHANG (2016)
The invention discloses an optimization method for a heat-engine plant thermal on-line process identification and control algorithm based on a dual-objective parallel ISLAND-HFC mixed model genetic programming algorithm. The steps comprise: 1, establishing a hardware platform; 2, the optimization method being completed by executing foreground interface software and background software by the hardware platform, the background software being formed by field test and data acquisition software, process identification software, and PID controller parameter optimization software. The method makes an ISLAND model and a HFC model organically combine together, anti-prematurity convergence property is good, multi-core CPU resources of an industrial control computer are fully used, multithreading run concurrently, evolution speed is fast, and the method is suitable to solve comprehensive problems. On one hand, dual-objective evolution controls errors between an evolution model and an ideal model, and on the other hand,